Mediating Effect of Work Motivation on Green Human Resource Management Practices and Employees’ Behavioural Outcomes - Salau O.P; Adeniji A.A; Falola H.O; Ohunakin F; Abasilim U. D; Chukwuemeke C.D. (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
Green human resource management practices have practically produced positive results for the environment. This arises as many organisational goals have been required to prioritise environmental problems and organisational sustainability due to emerging global environmental concerns. This does not suggest that the organisation should be painted green, but rather that the initiatives adopted by organisations in a specific sector are environmentally conscious of achieving required behavioural dispositions. But this may not be achieved without consistent work motivation. Hence, this research investigated the mediating effects of work motivation on Green HRM and employees’ behavioural outcomes in Nigeria's manufacturing industry. The Stakeholders’ theory was adopted for this study and it assumes that stakeholders have the power to persuade organisations to adopt environmental practices that result in better environmental outcomes. A descriptive survey research design was adopted to explain the mediating effect of work motivation on Green HRM and employees’ behavioural outcomes. An online questionnaire was employed and distributed to the selected manufacturing firms in Nigeria. This study focused on five (5) different manufacturing firms selected based on their performance, reputation, overall assets and ranking. The data for the study were analysed and presented using SPSS and SEM-PLS (Structural equation method). The findings indicated that motivation, to a great extent, mediates green HRM and employees’ behavioural outcomes. Additionally, the findings made it possible for Nigerian manufacturing companies to prioritize green HRM methods in order to boost employee motivation and reinforced behaviour. Based on the findings, it was proposed that managers in the sampled Nigerian manufacturing sector make an effort to give employees' participation in green activities to measure and evaluate organisational performance. Also, while embracing green HRM practices, the management of the Nigerian manufacturing sector should inspire their members of staff.